2013
DOI: 10.1016/j.foreco.2013.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Control of a major pest of forestry, Hylobius abietis, with entomopathogenic nematodes and fungi using eradicant and prophylactic strategies

Abstract: a b s t r a c tHylobius abietis, a major problem for seedling survival on forested land, develops under the bark of stumps of felled conifers. We investigated the efficacy of entomopathogenic nematodes (EPN) and fungi (EPF) applied to stumps to suppress adult emergence. We performed five field trials over three years and assessed results through destructive sampling and emergence trapping. We used two strategies in application: eradicant, where treatments were applied after weevil colonisation and prophylactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…Wegensteiner and Führer (1988) paid attention to very low mortality of H. abietis beetles attracted to the spruce bark treated with B. bassiana. Williams et al (2013) tried to reduce the numbers of H. abietis larvae developing in the stumps through the application of B. bassiana together with entomopathogenic nematodes (Sterneinema carpocapsae and Heterorhabditis downes) on these stumps. The results showed a higher effectiveness of nematodes (up to 50% mortality of larvae) compared to very low efficacy of fungus (up to 3.5% mortality of larvae).…”
Section: Discussionmentioning
confidence: 99%
“…Wegensteiner and Führer (1988) paid attention to very low mortality of H. abietis beetles attracted to the spruce bark treated with B. bassiana. Williams et al (2013) tried to reduce the numbers of H. abietis larvae developing in the stumps through the application of B. bassiana together with entomopathogenic nematodes (Sterneinema carpocapsae and Heterorhabditis downes) on these stumps. The results showed a higher effectiveness of nematodes (up to 50% mortality of larvae) compared to very low efficacy of fungus (up to 3.5% mortality of larvae).…”
Section: Discussionmentioning
confidence: 99%
“…Our trials at seven different sites over two years showed that H. downesi gave slightly better results but not significantly different from S. carpocapsae (Kapranas et al 2017), in contrast to earlier work showing that H. downesi was superior (Dillon et al 2006;Williams et al 2013a, b). Typically EPN suspension is applied directly to the soil around the stump (Dillon et al 2006;Williams et al 2013a;Kapranas et al 2017), but in our study we tested a modified method of application by applying the suspension on the top edges of the stump, targeting the gap between the bark and the wood (though some of the suspension will eventually make it to soil by spill over the stump). In the latter method it is likely that some nematodes were more exposed to UV light and desiccation and consequently died but, on the other hand, most of the nematodes entered the space between the wood and the bark and would have transferred, at least to some extent passively, along the rootways, thus reaching more quickly the weevils that are typically found there.…”
Section: Discussionmentioning
confidence: 99%
“…Traps were sampled every 2-4 weeks throughout the season, starting midJuly until weevil emergence ceased in NovemberDecember. General methods follow established protocols as described for previous studies (Williams et al 2013a;Kapranas et al 2017). …”
Section: Parasitism Rates and Efficacy Of Epn Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations